Prejudice Against Immigrants Symptomizes a Larger Syndrome, Is Strongly Diminished by Socioeconomic Development, and the UK Is Not an Outlier: Insights From the WVS, EVS, and EQLS Surveys - Evans, M. D. R.; Kelley, Jonathan (Frontiers in Sociology, 2019)
Public attitudes towards immigrants in the UK, especially prejudice against them, form a strong theme in retrospective media postmortems emphasizing the uniqueness of Brexit, yet similarly hostile public opinion on immigrants forms a recurrent theme in populist politics in many European Union nations. Indeed, if UK residents are not uniquely hostile, then the UK's exit from the EU may be only the first symptom of proliferating conflicts over immigration that will plague EU nations in future years. A well-established symptom (or consequence) of prejudice – aversion to outgroups as a neighbours – shows that prejudice against immigrants, other races, Muslims, Hindus, Jews, and Gypsies are all relatively low in the UK. This is as expected from the general decline of prejudice and social distance with socioeconomic development, demonstrated here in broad perspective across many countries. Indeed, UK residents are about as prejudiced against each of these ethno-religious outgroups as are their peers in other advanced EU and English-speaking nations, and much less prejudiced than their peers in less prosperous countries. Confirmatory factor analysis supports the view that a single latent ethno-religious prejudice generates all these specific prejudices, so it is not specific experiences with any one of these groups, nor their specific attributes, that are the wellspring of this deep-seated underlying prejudice. Replication using other measures of prejudice and another cross-national dataset confirms these findings. Data are from the pooled World and European Values Surveys (over 450,000 individuals, 300 surveys, and 100 nations for this analysis) and from the well-known European Quality of Life surveys. Analysis is by descriptive, multilevel (random intercept, fixed effects), and structural equation methods.